2017
DOI: 10.11646/phytotaxa.303.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Two new species segregated from Hymenophyllum tunbrigense (Hymenophyllaceae) in southern South America, based on morphological, anatomical, molecular and distributional evidence

Abstract: The cosmopolitan species Hymenophyllum tunbrigense was traditionally represented in southern South America by two allopatric varieties: H. tunbrigense var. tunbrigense in the Andean Patagonian forests of Argentina and Chile, and H. tunbrigense var. cordobense, an endemic taxon restricted to the mountain system of central and north-western Argentina. Given the diagnosable differences between these two taxa, and between these taxa and the European and African entity, based on morphological, anatomical, molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Similarly, Botrychium lunaria (L.) Swartz (Ophioglossaceae) or Hymenophyllum tunbrigense (L.) Sm. (Hymenophyllaceae), have traditionally been described as examples of bipolar disjunction, but Stensvold (2007) and Larsen et al (2017) showed that southern hemisphere populations of these two species form distinct taxonomic units. Conducting an accurate taxonomic reassessment as well as phylogenetic studies of bipolar species are particularly important because of the risk of parallel or convergent evolution in morphological traits, as an adaptation or evolutionary response to a harsh (extreme) environment (see below Hypotheses accounting for the bipolar distribution and Hypothesis testing of bipolar Carex ).…”
Section: Principles For the Study Of Disjunct (Bipolar) Speciesmentioning
confidence: 99%
“…Similarly, Botrychium lunaria (L.) Swartz (Ophioglossaceae) or Hymenophyllum tunbrigense (L.) Sm. (Hymenophyllaceae), have traditionally been described as examples of bipolar disjunction, but Stensvold (2007) and Larsen et al (2017) showed that southern hemisphere populations of these two species form distinct taxonomic units. Conducting an accurate taxonomic reassessment as well as phylogenetic studies of bipolar species are particularly important because of the risk of parallel or convergent evolution in morphological traits, as an adaptation or evolutionary response to a harsh (extreme) environment (see below Hypotheses accounting for the bipolar distribution and Hypothesis testing of bipolar Carex ).…”
Section: Principles For the Study Of Disjunct (Bipolar) Speciesmentioning
confidence: 99%
“…achalensis Hieron.) was proposed by Hieronymus (1896) for Argentine populations (Córdoba) of the H. tunbrigense complex, however, this name has already been clarified by Larsen et al (2017), as a heterotypic synonym of H. cordobense . Taxonomic studies with species complexes in H. subg.…”
Section: Discussionmentioning
confidence: 99%
“…DNA Sequencing and Phylogenetic Analyses —Phylogenetic analyses were performed using five regions of the plastid DNA, as previously used by Hennequin et al (2003, 2010) and Larsen at al. (2017), including two coding regions ( rbcL and rps4 ) and three spacer regions ( rps4-trnS, trnG-R, and rbcL-accD ). Sequences of 50 terminals, representing 37 species, were used in the phylogenetic reconstruction.…”
Section: Methodsmentioning
confidence: 99%
“…Comparative extant material was examined in the herbaria at the Field Museum (F) and the New York Botanical Garden (NY). Comparative data for extant Hymenophyllaceae were also obtained from available descriptions (e.g., Boodle, 1900; Copeland, 1937, 1938; Morton, 1968; Ogura, 1972; Iwatsuki, 1977; Tryon and Tryon, 1982; Tryon and Lugardon, 1991; Duckett et al, 1996; Dubuisson, 1997; Hennequin et al, 2003; Ebihara et al, 2006, 2007; Morbelli et al, 2010; Bauret et al, 2015; Arana et al, 2016; Nwe and Zhang, 2017; Larsen et al, 2017; Saïd et al, 2017). Fossil material described in this study is housed in the paleobotanical collections of the Field Museum, Chicago, Illinois (FMNH: collection numbers with the prefix PP).…”
Section: Methodsmentioning
confidence: 99%